A Common 3′UTR Variant of the PHOX2B Gene Is Associated With Infant Life-Threatening and Sudden Death Events in the Italian Population - Bachetti, Tiziana; Bagnasco, Simona; Piumelli, Raffaele; Palmieri, Antonella; Ceccherini, Isabella (Frontiers in Neurology, 2021)
Heterozygous mutations in the Paired like homeobox 2b (PHOX2B) gene are causative of congenital central hypoventilation syndrome (CCHS), a rare monogenic disorder belonging to the family of neurocristopathies and due to a defective development of the autonomic nervous system. Most patients manifest sudden symptoms within 1 year of birth, mainly represented by central apnea and cyanosis episodes. The sudden appearance of hypoxic manifestations in CCHS and their occurrence during sleep resemble two other unexplained perinatal disorders, apparent life-threatening event (ALTE) and sudden and unexpected infant death (SUID), among which the vast majority is represented by sudden infant death syndrome (SIDS). Differently from CCHS, characterized by Mendelian autosomal dominant inheritance, ALTE and SIDS are complex traits, where common genetic variants, together with external factors, may exert an additive effect with symptoms likely manifesting only over a “threshold.” Given the similarities observed among the three abovementioned perinatal disorders, in this work, we have analyzed the frequency of PHOX2B common variants in two groups of Italian idiopathic ALTE (IALTE) and SUIDs/SIDS patients. Here, we report that the c*161G>A (rs114290493) SNP of the 3′UTR PHOX2B (i) became overrepresented in the two sets of patients compared to population matched healthy controls, and (ii) associated with decreased PHOX2B gene expression, likely mediated by miR-204, a microRNA already known to bind the 3′UTR of the PHOX2B gene. Overall, these results suggest that, at least in the Italian population, the SNP c*161G>A (rs114290493) does contribute, presumably in association with others mutations or polymorphisms, to confer susceptibility to sudden unexplained perinatal life-threatening or fatal disorders by increasing the effect of miR-204 in inducing PHOX2B expression down-regulation. However, these are preliminary observations that need to be confirmed on larger cohorts to achieve a clinical relevance.